Postpartum Depressive Symptoms and Experiences During COVID-19. Issue 2 (March 2022) - Goyal, Deepika; Beck, Cheryl Tatano; Webb, Rebecca; Ayers, Susan
Abstract: Purpose: To identify postpartum depression risk and describe experiences of women in the first 6 weeks after giving birth during the COVID-19 pandemic. Study Design and Methods: Using a convergent mixed-methods approach, we recruited a convenience sample of women living in the United States who gave birth March 1, 2020 or later from social media Web sites. Participants completed the Postpartum Depression Screening Scale-Short Form and provided written answers to open-ended questions regarding their experiences at home with their new infant. Results: Our 262 participants were on average 32.6 years of age, the majority were White (82%), married or partnered (91.9%), and college educated (87.4%). Mean postpartum depression score was 17.7 ( SD = 5.9) with 75% scoring ≥14, indicating significant postpartum depressive symptoms. Qualitative content analysis revealed five themes: Isolation and seclusion continue ; Fear, anxiety, and stress filled the days ; Grieving the loss of normal: It's just so sad ; Complicated by postpartum depression: A dark time ; and There is a silver lining . Quantitative and qualitative findings provided a holistic view of women's depressive symptoms and experiences at home with their infants during the COVID-19 pandemic. Clinical Implications: Although policies that reduce risk of COVID-19 exposure and infection for patients and the health care team must continue to be implemented, the adverse effects of depressive symptoms on maternal–infant wellbeing within the context of increased isolation due to the pandemic need to be kept at the forefront. Nurses need to be aware of the consequences of women sheltering in place and social distancing on maternal–infant outcomes, particularly on depression and likelihood of breastfeeding. Abstract : Women experienced more postpartum depressive symptoms while trying to navigate the challenges of the COVID-19 pandemic than expected, based on prepandemic postpartum depression prevalence data. Seclusion and having minimal help with the new baby were noted to be very stressful for many new mothers. Some mothers expressed positive aspects of COVID-19 related postpartum isolation as being blessings in disguise and a silver lining because they were able to bond with the new baby and their partners while learning parenting together.